2022
DOI: 10.1002/bio.4409
|View full text |Cite
|
Sign up to set email alerts
|

Facile one‐pot synthesis of fluorescent aminoclay and the applications for fluorescence sensing Cr2O72−

Abstract: Here, we developed a facile one-pot strategy for the fabrication of fluorescent aminoclay (F-AC) through in situ solvothermal treatment of 3-aminopropyltrimethoxysilane, MgCl 2 , and sodium ascorbate at 180 C for 6 h. The obtained F-AC exhibited blue emission, good water solubility, and satisfactory photostability. It was observed that Cr 2 O 7 2À could selectively quench the fluorescence of F-AC through the inner filter effect and static quenching process.As a result, a novel fluorescent F-AC-based nanosensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…These materials could be used for unwanted signal noise suppression. Furthermore, Guo et al [45] reported a one-pot method for synthesizing fluorescent aminoclay (F-AC) through a solvothermal method. They found that the fabricated F-AC produced a blue emission, excellent photostability, and good solubility.…”
Section: Overview Of Published Researchmentioning
confidence: 99%
“…These materials could be used for unwanted signal noise suppression. Furthermore, Guo et al [45] reported a one-pot method for synthesizing fluorescent aminoclay (F-AC) through a solvothermal method. They found that the fabricated F-AC produced a blue emission, excellent photostability, and good solubility.…”
Section: Overview Of Published Researchmentioning
confidence: 99%